(untitled) (REMUNOM, 2026)
This article analyzes the custody hearing as an instrument for guaranteeing fundamental rights in the Brazilian criminal justice system. This institution ensures that every person arrested is promptly presented to a judicial authority for evaluation of the legality of the arrest and verification of any mistreatment or abuse. In Brazil, its regulation occurred with Resolution No. 213/2015 of the National Council of Justice, in accordance with international commitments assumed by the Brazilian State, especially the American Convention on Human Rights. The study aims to examine the legal foundations of the custody hearing and the challenges related to its effectiveness in the Brazilian penal system. This is a bibliographic and documentary research, with a qualitative approach, exploratory and descriptive in nature, guided by the deductive method. The results indicate that the custody hearing contributes to the control of pretrial detentions and to the prevention of institutional abuses. However, structural challenges persist that limit its full implementation, especially in regions with less developed justice system infrastructure. It is concluded that institutional strengthening and the expansion of human and material resources are essential to ensure greater effectiveness of the institution and consolidate the protection of fundamental rights in the contemporary Brazilian criminal process, and to promote greater respect for the individual guarantees of people.